2007
DOI: 10.1111/j.1467-9507.2007.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Victimization Within Mutually Antipathetic Peer Relationships

Abstract: Children's victimization experiences within relationships characterized by mutual animosity were examined among 210 6th-and 7th-grade boys and girls. Participants reported that a greater proportion of mutual antipathies, relative to other peers, victimized them. Moreover, the receipt of victimization within antipathetic relationships was greater when the partner in the relationship was aggressive, physically strong, non-victimized and had low levels of internalizing problems. Perceptions of victimization and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 53 publications
(72 reference statements)
3
73
0
Order By: Relevance
“…There is accumulating evidence showing that aggressive behavior is highly relationship specific, more commonly occurring in dyads characterized by unilateral or mutual dislike than in positive relationships such as friendships (Card & Hodges, 2007;Peets, Hodges, & Salmivalli, 2008). However, this does not mean that positively laden relationships are conflict free (e.g., Hartup, French, Laursen, Johnston, & Ogawa, 1993;Hartup, Laursen, Stewart, & Eastenson, 1988) or that aggressive (or bullying) behavior is never evidenced within friendships (Grotpeter & Crick, 1996;Mishna, Wiener, & Pepler, 2008).…”
Section: Role Of Relationship Contextmentioning
confidence: 96%
“…There is accumulating evidence showing that aggressive behavior is highly relationship specific, more commonly occurring in dyads characterized by unilateral or mutual dislike than in positive relationships such as friendships (Card & Hodges, 2007;Peets, Hodges, & Salmivalli, 2008). However, this does not mean that positively laden relationships are conflict free (e.g., Hartup, French, Laursen, Johnston, & Ogawa, 1993;Hartup, Laursen, Stewart, & Eastenson, 1988) or that aggressive (or bullying) behavior is never evidenced within friendships (Grotpeter & Crick, 1996;Mishna, Wiener, & Pepler, 2008).…”
Section: Role Of Relationship Contextmentioning
confidence: 96%
“…Hodges et al (1997) found that the number of friends a child held correlated negatively with victimization, and that adjustment problems onset by victimization diminished as friends increased. The social experience for victimized children may also involve negative interactions such as antipathies or enmities, or children who mutually reject each other (Hartup 2003;; however, less is known regarding possible associations between antipathetic interactions and victimization (Card and Hodges 2007).…”
Section: Social Status and Interpersonal Relationshipsmentioning
confidence: 99%
“…Victims of bullying often exhibit difficulties in social understanding (Garner and Stowe Hinton 2010), occupy low social status (Card and Hodges 2007), and are perceived as 'different' or deviating from peer group norms (Horowitz et al 2004). The social experience of children with ASC reads remarkably similarly.…”
Section: What Is Bullying?mentioning
confidence: 99%